Integration of Information Communication Technology in Teaching: The Underpinning Factors Among Kenya’s Primary School Teachers - Sammy Muteti Mutisya (Commonwealth of Learning, 2020)
This study was carried out with 86 primary school teachers in Kenya’s Narok County and explored factors affecting integration of ICT in teaching and learning. Multiple regression was used for data analysis. The results revealed that 32.5% of the variance was explained by the independent and extraneous variables (R2 =0.325, P=0.001) and was statistical significant. Attitude was found to be a significant predictor of teachers’ behavioural intention to use ICT in teaching and learning (β=0.259, p<0.05) while Performance expectancy (β=0.148, p>0.05), Effort expectancy (β=-0.185, p>0.05), Social influence (β=0.029, p>0.05), facilitating condition (β=0.194, p>0.05), Self-efficacy (β=0.195, p>0.05) and anxiety (β=0.074, p>0.05) were not significant predictors. The study recommends training of teachers on subject specific ICT technologies, laptops and computers be availed for use by teachers and pupils, school heads be trained on how to monitor and support integration of ICT by teachers and governments to provide schools with requisite ICT infrastructures.